Florida 4-H Junior Project Report - Laura Cash; Geralyn Sachs; Christopher DeCubellis; Marnie Ward; Dallas Meringolo; Sarah Thomas Hensley; Andrew Toelle; Laura Valencia (EDIS)
This report form is to be completed by junior (age 8–10) 4-H members as a record of their 4-H project completion. Project Reports should be turned in annually at the end of the 4-H year to their county 4-H agent. This 10-page major revision was compiled by the Florida 4-H Awards and Recognition Task Force; Geralyn Sachs and Laura Cash, chairs. https://edis.ifas.ufl.edu/4h033